Color Removal of Pulp and Paper Mill Wastewater Using Residual Eucalyptus Wood: 10.32526/ennrj/20/202200038 - Yupin, Kanjana; Neamhom, Thanakrit; Singhkant, Chatchawal; Sreesai, Siranee; Polprasert, Supawadee (Environment and Natural Resources Journal, 2022)
This study investigated the color removal efficiency of pulp and paper mill wastewater using residual eucalyptus wood as a method to minimize the solid wastes generated from pulp and paper processes. The activated carbon used in this study as the color adsorbent was produced from residual eucalyptus wood. The carbon was activated with phosphoric acid and carbonized in a furnace at 500°C for 60 min. Effects of types and amounts of activated carbon on color removal efficiency were evaluated. Three types of solid wastes, consisting of wood chip, bark, and mixed wood (wood chip:bark, 1:1), were investigated at a loading of 1, 3, 5, and 7 g/100 mL under contact times of 30, 60, 90, and 120 min. The results showed that 7 g of wood chip activated carbon/100 mL under all contact times gave color removal efficiency of 94-97%. However, the highest adsorption capacity of 216 ADMI/g occurred at 1 g of adsorbent used. Freundlich isotherms were satisfactorily fitted to experimental data for the best condition with high correlation coefficients. The color removal efficiency depended on surface area, pore volume, structure, and characteristics of the activated carbon.